Cosmic radiation shielding property of boron reinforced continuous fiber nanocomposites produced by electrospinning - Ozcan, Muecahid; Kaya, Cengiz; Kaya, Figen (SPRINGER, 2023)
Electrospinning, a cutting-edge production technique, is used to create boron-reinforced continuous fiber nanocomposites that shield space missions from cosmic radiation, a significant hazard. By incorporating boron, which is known for its exceptional neutron shielding properties, into the polymer matrix, a composite material that is flexible, lightweight, and highly resistant to radiation is produced. The results indicate that continuous fiber nanocomposites reinforced with boron, boric acid, or both have a high shielding efficiency against cosmic radiation. The adaptability and low weight of the manufactured nanocomposites make them ideal for space applications. While boric acid combines with PVA at the molecular level and alters the molecular chain structure of PVA, it is believed that elemental boron is only incorporated as particulates into the PVA polymer. It is known that both boric acid and elemental boron doped nanocomposites provide samples with a thickness of 10 microns with 13.56% neutron shielding and superior photon blocking ability.
Keywords: Radiation shielding; Nanocomposite; Electrospinning; Polyvinyl alcohol; Boron; EXPOSURE; Science & Technology - Other Topics; Materials Science; Physics